Reactivity of a Methoxido–Ruthenium Complex Bearing a Pincer‐Type Bis(carbene) Ligand toward Thiocyanate, Carbon Disulfide, and Isothiocyanate. Issue 5 (3rd February 2017) - Arikawa, Yasuhiro; Nakamura, Takuo; Higashi, Takefumi; Horiuchi, Shinnosuke; Sakuda, Eri; Umakoshi, Keisuke
Abstract : Thiocyanate linkage isomers and two insertion complexes were prepared from a methoxido–ruthenium complex bearing a 2, 6‐bis(3‐ tert ‐butylimidazol‐2‐ylidene)pyridine (CNC) and a bipyridine ligand. In the mixture of the linkage isomers obtained from the substitution reaction, a linear N‐bound and a bent S‐bound isomer were crystallographically determined, and the equilibrium between them at elevated temperature was revealed. On the other hand, in reactions with carbon disulfide (CS2 ) and phenyl isothiocyanate (PhNCS), the S=C bond was inserted into the Ru–OMe bond, and the resulting ligands are bound to the ruthenium center by the sulfur atom. Abstract : Thiocyanate linkage isomers and two insertion complexes were prepared from a methoxido–ruthenium complex bearing a pyridine‐based bis(carbene) (CNC) and a bipyridine ligand. A linear N‐bound and a bent S‐bound linkage isomer were crystallographically determined. In reactions with carbon disulfide and phenyl isothiocyanate the S=C bond was inserted into the Ru–OMe bond.